E-Learning for Health-Care Workforce Development - Taylor, L.; Abbott, P. A.; Hudson, K. (Yearbook of Medical Informatics, 2008)
Objectives To summarize advances in informatics that contribute to scaling-up the health care workforce.Method A review of projects and methods in information and communication technologies (ICT) that are having an impact on educating frontline health care workers.Results and conclusionse-learning is providing innovative approaches for health workforce development, especially in underserved areas.
Keywords: e-learning; information and communication technology (ICT); health workforce development; scale-up and retention